Novel traits for genetic selection in Gelbvieh influenced cattle - White, Kari L. (Kansas State University, 2020)
The objective of this research is to add needed information on economically relevant traits (ERT) to the existing American Gelbvieh Association National Cattle Evaluation. Substantive pieces were added to that vision by identifying selection tools that have not previously been established for that evaluation, or by re-assessing current selection tools to include the most efficient analysis. The topics of research included are traits that are often difficult or expensive to measure, which will benefit the greatest from further research into developing efficient and effective selection tools. The objectives of the feed energy utilization study were to estimate genetic parameters for dry matter intake (DMI), percent daily dry matter required (PDMR), residual feed intake (RFI), adjusted weaning weight (AWWT), and post weaning gain (PWG) in a multi-breed population of growing beef cattle, in addition to implementing an economic selection index identify genetically favorable animals in the complex of traits associated with feed energy utilization. Feed intake and performance data for this analysis included records on animals collected by twelve individual breeders using Growsafe® systems and were later submitted to the AGA. Feed efficiency parameters were estimated to be moderately heritable in this data set of Gelbvieh influenced cattle, indicating producers can make genetic improvement through selection for the traits. In addition, correlations among certain feed efficiency traits indicate selection for one trait should result in a correlated response in others. Index selection is preferable for genetic improvement in feed efficiency traits because of a large unfavorable genetic correlation between feed intake and growth. Continued collection of feed efficiency phenotypes is essential to identifying animals that are profitable in feed energy utilization. The objectives of the sustained productivity study were to calculate an estimated breeding value (EBV) for each sire for relative risk of failing to calve consecutively within 425 days from 1 to 9 parities. The EBV for relative risk could then be used as genetic selection tool for sires whose daughters are more likely to reproduce in the herd within 425 days from 1 to 9 parities. Data for this analysis were birth dates and disposal codes reported by breeders to the AGA. Every animal in the AGA database has an associated code. For the purposes of this analysis, a female was considered to have a complete record (uncensored, code “0”) if she failed to calve within 425 days of the previous calving, with no reported disposal code. A female was also considered uncensored, or considered to have a complete record, if she was greater than 11 years and 60 days old at the time of data extraction without a calving interval greater than 425 days in her lifetime. A female was considered to have an incomplete record (censored, code 1) if she had a defined non-reproductive disposal code, indicating she was culled from the herd for a reason other than reproduction. Females still active and producing in the herd at the time of data extract were also considered censored, since the upper bound of their productive life was still unknown. Analysis indicated that animals in our data set that failed to calve within 425 days of previous calving, or those who were still producing in the herd at 11 years 60 days of age (uncensored) exited the herd at an average of 2.19 years old. Animals with a defined non-reproductive disposal code, or those still active in the herd at less than 11 years 60 days of age (censored) exited the herd at an average of 2.39 years old. Younger parities had a greater culling rate that decreased at later parities. This indicates failure occurs at a higher rate at younger ages. It should be noted that while it appears younger parities have a greater risk of failure, animals most likely to be culled for reproductive failure have already left the herd by later parities. As a result, culling rate is lower in advanced parities. Sustained reproductive success and length of productive life as indicators of cow fertility are of great economic importance to the beef industry. The current study is a prototype genetic evaluation that will allow the AGA to select for sires that have daughters with improved length of productive life. The objectives of the tenderness study were to quantify the genetic and phenotypic relationships between various methods of tenderness evaluation for fresh and frozen samples, quantitatively estimate breed effects of tenderness, and to assess the interaction of breed with calpastatin (CAST) and µ-calpain (CAPN1) markers. Data used in this analysis included SSF predicted by visible spectroscopy (LED), visible/near-infrared hyperspectral imaging (VISNIR) predicted SSF, fresh and frozen SSF aged to approximately 14 days (SSF14), frozen SSF aged to approximately 3 and 4 days combined (SSF3), and frozen WBSF aged to approximately 14 days and 3 and 4 days combined (WBS14 and WBS3). Predicted measures of meat tenderness (LED and VISNIR) were estimated to be highly heritable at 0.78 and 0.59, respectively. High heritability in predicted measures of tenderness indicate they may be useful as correlated traits for selection. Slice shear force 3 and WBS3 had the greatest genetic correlation of 0.93 (0.03). Genetic correlations between estimated tenderness values (LED and VIS) and measured tenderness values (SSF and WBSF) ranged from low (0.02) to moderate (0.36) for LED and from low (-0.01) to moderate (0.48) for VIS. Warner-Bratzler shear force values at different days of post-mortem aging were found to be highly genetically correlated at 0.81 (0.05). Genetic correlations between SSF and WBSF values ranged from moderate (0.39) to high (0.93) depending on age. Breed was found to be a significant effect at p < 0.05 for LED, VISNIR, SSF14, SSF3, and WBS14. Individual breed effects relative to Angus suggest variation between breeds when selecting for meat tenderness. Non-zero breed effects would be important to include in multi-breed genetic evaluations of tenderness to ensure accurate predictions of genetic merit. Multiple markers on both CAPN1 and CAST were found to be associated with each trait, indicating marker assisted selection could be employed as a selection tool for post-mortem tenderness. Our data did not indicate a significant interaction between breed and marker, which suggests markers significantly associated with tenderness phenotypes traits may possibly be used for animals from a wide variety of breed groups. Results from this study provide an opportunity to use marker data from USMARC to estimate genomic enhanced tenderness for Gelbvieh influenced cattle because there is a lack of significant interaction between breed and marker.
Keywords: Beef cattle; genetics; tenderness; Feed efficiency